VANET Data Dissemination an Emerging Technology: A Survey - Gupta, Deepak; Rathi, Rakesh; Gupta, Shikha; Sharma, Neetu (International Journal of Computer Sciences and Engineering, 2020)
Vehicular Ad hoc Networks (VANET) is an emerging technology and is type of an ad hoc mobile network which offered facilities like security, traffic proficiency, driving ease, traffic management services etc. with the help of vehicles communications. Traffic information is especially useful for the driver during driving, such as an accident alert or else traffic jam alert. In ad hoc vehicle networks, data transmission is usually performed by multi hop communication in which high-speed vehicles act as a data carrier. Vehicles are forced to navigate a defined route, depending on the route layout and traffic conditions. In an ad hoc vehicle network, delivering data to multiple stores is a very complicated job because of the high mobility and frequent disconnections that occur in vehicle networks. The biggest challenge in ad hoc vehicle networks is to gather information such as accidents, speed limits, road obstacles, road conditions, traffic conditions, commercial advertising, etc. for safety and convenience. In many diffusion techniques, the vehicle transports the package until it finds another vehicle heading towards destination and at that point passes the package to that vehicle. In this article we surveyed some research paper based on predictive data dissemination and try to put forward their research work. The surveyed research papers are based on different techniques and tools for data dissemination protocols.